A systematic review of treatment strategies to combat acute and chronic rejection episodes in vascularized composite allotransplantation - Knoedler, Leonard; Niederegger, Tobias; Schaschinger, Thomas; Hundeshagen, Gabriel; Munzinger, Robert; Heiland, Max; Cetrulo, Curtis L.; Lellouch, Alexandre G. (Frontiers in Immunology, 2026)
BackgroundVascularized composite allotransplantation (VCA) offers unique reconstructive solutions for severe tissue loss, restoring form and function. Acute and chronic rejection remains a significant barrier, with acute episodes occurring in most recipients and chronic rejection persisting as the leading cause of graft failure. Unlike solid organ transplantation, VCA involves highly immunogenic tissues, like skin and mucosa, making rejection more frequent and challenging to manage.MethodsA systematic review was conducted following PRISMA 2020, searching PubMed/MEDLINE, EMBASE, and Web of Science for original human VCA studies reporting immunosuppressive protocols and outcomes in acute or chronic rejection. Quality was assessed using the Newcastle–Ottawa Scale and Level of Evidence; extracted data included demographics, regimens, rejection episodes, treatments, and graft survival.ResultsFourty-six studies (136 recipients) met inclusion criteria: upper extremity (n=69; 51%), face (n=33; 24%), abdominal wall (n=33; 24%), scalp and penile (each n=1; 0.7%). Acute rejection occurred in 81/136 (60%) within year 1, most often at POW 1–2 (n=52), 5–12 (n=42), and 13–52 (n=30). Severity was Banff grade I (n=49; 36%), II (n=73; 54%), III (n=50; 37%), and severe IV (n=1; 0.7%). Common symptoms included skin lesions (n=43; 32%), edema (n=32; 24%), erythema (n=29; 21%), and rash (n=15; 11%), with some experiencing numbness (n=4; 2.9%), tingling (n=5; 3.7%), or burning sensations (n=5; 3.7%). Corticosteroids were the mainstay (n=98; 72%)—methylprednisolone (n=31; 23%), clobetasol (n=15; 11%), and prednisone (n=11; 8.1%); tacrolimus was used in 49 (36%), including topical in 29 (21%). Other immunosuppressants included antithymocyte globulin (n=19; 14%), alemtuzumab (n=11; 8.1%), mycophenolate mofetil (n=11; 8.1%), and rituximab (n=6; 4.4%); basiliximab (n=4; 2.9%), sirolimus (n=2; 1.5%), and plasmapheresis (n=4; 2.9%) were used selectively. Monotherapy was used in 42 episodes, and dual therapy in 51, most commonly methylprednisolone plus topical tacrolimus (n=26).ConclusionThis review underscores the ongoing challenge of rejection in VCA and the need for improved treatment strategies, with corticosteroids, calcineurin inhibitors, and mycophenolate mofetil remaining standard while emerging biologicals offer promise. Acute rejection is often manageable yet threatens graft survival, whereas chronic rejection is less reported, likely under-recognized and harder to treat, underscoring need for novel immunomodulators, standardized protocols, and prevention to improve outcomes.